Through Exchange: Karatani Compared With Marx - Di Mino, Vincenzo Maria (Identities: Journal for Politics, Gender and Culture, 2021)
The following paper has as its object the political philosophy of K. Karatani, in particular its relationship with the work of Marx. Japanese philosopher, in fact, reinterprets some elements of Marxian theory in the light of Kantian categories, hybridizing the ethical and moral theory of the latter with the critique of the political economy of the former. The result of Karatani’s project can be seen, in particular, in two works. With the first, Transcritique, Karatani moves into the realm of philosophy to construct a method that holds the two theoretical poles together. The concept of ’Transcritique’, in fact, represents the junction between Kantian and Marxian insights. With the second work, ’The Structure of World History’, the Japanese philosopher shifts the analytical focus from ethics to economics, proposing a different interpretation of capitalism and its historical cycles. The shift of the observation of the capitalist system from the sphere of production to that of exchange represents the analytical novelty. Carrying through to the end the methodology developed in the previous work, Karatani traces back to exchange all the productive, institutional and political dynamics produced over time. Cycles of accumulation thus become cycles of exchange. The author, in fact, determines a correspondence between the specific modes of exchange and the consequent political structures, highlighting the centrality that money occupies, both in the theoretical elaboration and in political reality. The prevailing mode of production, based on the exchange of commodities, relies on the absolute mobility of money and on the strength of the state political institution, which acts as a hinge between the global dimension of exchanges and the territorial need for the appropriation of surplus-value. Karatani’s critique is embodied in a political proposal, articulated through two key figures: community and cosmopolitanism. With the first term, the philosopher opposes the materiality of human relationships based on reciprocity to the abstract equivalence of economic relationships. By the second term, he shows the need for an extended political practice in which the pursuit of local freedom goes hand in hand with the realization of global justice. The paper traces these themes both through direct exposure of Karatani’s work and by offering critical comparisons with other authors who have addressed similar issues. Finally, the purpose of this paper is to emphasize the originality of the Japanese author’s philosophical-historical work, suspended between utopia and pragmatism, also through criticism, in order to highlight its strengths and underline its potential weaknesses. Author(s): Vincenzo Maria Di Mino Title (English): Through Exchange: Karatani Compared With Marx Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 18, No. 1-2 (2021). Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 8-20 Page Count: 13 Citation (English): Vincenzo Maria Di Mino, “Through Exchange: Karatani Compared With Marx,” Identities: Journal for Politics, Gender and Culture, Vol. 18, No. 1-2 (2021): 8-20. Author Biography Vincenzo Maria Di Mino, Independent researcher Vincenzo Maria Di Mino (1987) is an independent researcher on political and social theory